Developing Flipbooks Teaching Material Based on Local Wisdom in Improving Young Learners’ Writing Skills of Descriptive Texts - Rahmawati, Yulia; Purwati, Panca Dewi (JOLLT Journal of Languages and Language Teaching, 2025)
The environment is the main source of learning. The ability of students to understand the descriptive texts and writing these is still low. The use of teaching materials in learning is less close to student life. The availability of learning resources is still limited. Students can read but have not been able to understand the content of the material. This study aims to determine the feasibility and effectiveness of flipbook teaching materials based on local wisdom in improving learning outcomes by analyzing the description text of grade V elementary school students. The method in this study uses the type of Research and Development (R&D) research with the Borg and Gall development model. Product validity tests are carried out with material expert validators and media expert validators.Â The results of this study showed that the results of the media feasibility test obtained were 93.75% with a very feasible predicate and the feasibility test results from material experts were 93.75% with a very feasible predicate. The results of large-scale usage trials showed an increase from pretest to posttest with an average N-Gain of 0.4 and significance (2-tailed) of 0.000 < 0.05. Flipbook teaching materials display designs and materials conceptualized according to the local wisdom of the Tegal Regency. The conclusion of the results of this study shows that flipbook teaching materials based on local wisdom are declared feasible and effective in improving learning outcomes by analyzing the decriptive texts.